Pharmacotherapeutic Approaches in Tobacco Cessation and its Challenges: A Review - Akshyata Panda1 , Anurag Satpathy2 , Rinkee Mohanty3 , Rashmita Nayak2 , Abhaya Chandra Das4 , Saura (Institute of Medico-legal Publications Pvt Ltd, 2020)
Tobacco use is a global menace and leading cause of cancers and death. Tobacco cessation strategies arebeing formulated world over to curb this problem. Nicotine replacement therapy (NRT) such as chewinggum, patches and inhaler and drugs like Bupropion have shown some success in smoking cessation rates inthe short and long terms